Kinematics in Bulk Volumes - Steinmann, Paul (Spatial and Material Forces in Nonlinear Continuum Mechanics, 2022)
This chapter recalls the pertinent spatial and material continuum kinematics in bulk volumes, thereby focusing on the nonlinear deformation maps, their associated tangent, cotangent and measure maps, and expresses their compatibility conditions.
CRIS-Team Scopus Importer:2022-04-15